Lean Manufacturing Analysis Using Waste Assessment Model (WAM) and Root Cause Analysis (RCA) Methods - Hidayatullah, Muhammad Asyrof; Pudji Widjajati, Endang (Universitas Trunojoyo Madura, 2024)
The rapid development of science and technology in the industrial world, causing competition between industries to be tighter. This makes the industry to increase productivity both in terms of process and results. Waste is a big problem in the industrial world. One of them occurred in a tissue industry in East Java. Where the production of towel wipes is one of the largest produced production items. The observations made identified 32 types of waste categorized into seven waste. Waste Assessment Model (WAM) is a suitable method to identify critical waste that occurs, Value Stream Mapping for mapping, Root Cause Analysis to find the root cause of problems, and 5W1H to reinforce problems and provide suggestions for improvement. The calculation and analysis results of the Waste Assessment Model (WAM) method obtained the largest amount of critical waste, namely defects by 20.31%, by 18.59%, and Motion by 15.30%. The root cause of the problem that occurs is the condition of the engine in a state that is not optimal age and lack of maintenance, the absence of SOPs that regulate how to maintain the appropriate order, human errors in the rewinder engine setup, and the need for engine upgrades. So that some recommendations for improvements that can be made are starting from the development of SOPs, training and monitoring, upgrading various facilities, and machine automation. The results of Value Stream Mapping (VSM) showed that the Value Cycle Efficiency (PCE) after improvement increased from 45.26 to 64.38%. This shows the success of improvement recommendations in resolving various wastes and increasing the efficiency of existing processes.